CALL, Self-Access, and Autonomous Learning - Jorge E. Benavides B. (Asociación Colombiana de Profesores de Ingles, 2016)
The idea of autonomous learning through a process of self-access learning is a very powerful one since CALL (Computer-Assisted Language Learning) can provide environments which could cope with a large variety of learning possibilities and learning styles. The autonomous computer user is free to choose his own course, topics, and work at his own pace. However, in this approach, high motivation may not necessarily mean learning efficiently. The student may not be very good at selecting his own learning strategy, especially at initial stages. This problem could be alleviated if the introduction of learning autonomy, through self-access learning, is done as a process where the learner is being trained to progressively go from an externally-directed learning approach to a self-directed learning approach (Benavides, 1995).